The Contribution of Dance and Drum Band Activities to the Gross Motor Development of Early Childhood at TK Negeri 1 Labuapi - Annisa Failasufa; I Wayan Karta; Dadi Setiadi (International Journal on Integrated Education, 2026)
This study aims to analyze the contribution of dance and drum band activities to the gross motor development of early childhood at TK Negeri 1 Labuapi. The study employed a quantitative approach with an ex post facto design involving 30 children in Group B. Data were collected using observation sheets for dance activities, drum band activities, and the Test of Gross Motor Development-2 (TGMD-2). Data analysis was conducted using simple regression and multiple regression tests with the assistance of IBM SPSS 23. The results showed that dance activities contributed significantly to gross motor development, with a significance value of 0.032 and a contribution of 15.3%. Drum band activities also contributed significantly, with a significance value of 0.019 and a contribution of 18.1%. Simultaneously, dance and drum band activities made a significant contribution to gross motor development, with an R Square value of 46.0%. The drum band variable was the most dominant variable influencing the gross motor development of early childhood children.